2014
DOI: 10.15740/has/arjci/5.2/166-171
|View full text |Cite
|
Sign up to set email alerts
|

Performance of black gram [Vigna mungo (L.) Hepper] varieties to different sowing dates

Abstract: : 30 days after onset of monsoon (20 th July) and three varieties in sub plot viz., V 1 -TAU-1, V 2 -BDU-1, V 3 -TPU-4. Gross and net plot size viz., 4.5 m x 4.4 m and 3.9 m x 4.0 m, respectively. The soil was medium black, clayey in texture, alkaline in reaction and higher in total soluble salt concentration, low in nitrogen and rich in phosphorus, potassium and lime, alkaline in reaction with high base saturation. Sowing was done by dibbling method. From the result of experiment it can be concluded that, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…This increase in seed yield of blackgram varieties might be due to the higher production efficiency that has been reflected through improvement in different yield attributing characters. Sunil et al (2020), Mane et al (2018), andJadhav et al (2014) also found similar results in the study. The maximum grain yield of blackgram (1306.70 kg ha −1 ) was observed in clipping of 1 st basal leaf, and the minimum (1127.30 kg ha −1 ) was observed in clipping of total apical leaves having no inflorescence treatment.…”
Section: Seed Yieldsupporting
confidence: 87%
“…This increase in seed yield of blackgram varieties might be due to the higher production efficiency that has been reflected through improvement in different yield attributing characters. Sunil et al (2020), Mane et al (2018), andJadhav et al (2014) also found similar results in the study. The maximum grain yield of blackgram (1306.70 kg ha −1 ) was observed in clipping of 1 st basal leaf, and the minimum (1127.30 kg ha −1 ) was observed in clipping of total apical leaves having no inflorescence treatment.…”
Section: Seed Yieldsupporting
confidence: 87%
“…This might be due to cultivar's genetic makeup and its capacity to adapt to a particular environmental condition in which it getting established. Similar findings were reported byJadhav et al (2014) andAggarwal et al (2014) in blackgram.…”
supporting
confidence: 91%
“…number of pods/plant, seeds/pod and seed weight/plant was significantly superior over the two varieties (Table 2). The probable reason for this may be improved photosynthetic activity due to increased source capacity and efficient translocation of photosynthates to the seed (Jadhav et al, 2014). The blackgram cultivar Mash 114 recorded higher seed yield (10.19 q/ha) and straw yield (26.47q/ha) which was significantly superior over Mash 338 and KUG 479.…”
Section: Discussionmentioning
confidence: 98%